A GERONTOLOGIA INTERFACE O MEIO AMBIENTE COMO ESTRATÉGIA NO CUIDADO E PROMOÇÃO DA SAÚDE - Cassol, Paulo Barrozo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704959 The demographic and epidemiological transition is resulting in global population aging, thisphenomenon is at different stages in the world, requiring a reorganization of Health Populationaging in Brazil is growing in numbers, approaching the values of developed countries, however thequestion social does not follow this path. This study aims to stimulate discussion of the need forpublic policies on elderly care interface with the Health and Environment as a strategy for care andhealth promotion. It is grounded in a theoretical study of literature. We conclude that healthpromotion involves the educational and environmental support. The interdisciplinarity of courseswith the health of natural areas is one way to develop innovative approaches to finding solutionsand promoting health for the elderly interface environment. The Environment and health areinextricably linked, in that case the relationship between humans and the environment may befavorable or detrimental to health, so your compression is essential for health promotion